Career exploration in early adulthood: The role of perceived future employability and career aspirations - Puspitasari, Lutfiana Putri; Widyowati , Arini (Universitas Ahmad Dahlan, 2025)
Career exploration is an important factor in shaping young adults’ future career goals. However, many young people struggle with limited self-understanding and a lack of awareness of available career options, which directly hinders their ability to engage effectively in career exploration. Despite the importance of career exploration, empirical evidence examining how perceived future employability and career aspiration jointly influence career exploration among young adults remains limited, making it difficult to design effective interventions to support students’ career development. This study aims to examine the relationship between perceived future employability, career aspiration and career exploration among young adults. A quantitative approach was employed using scales as data collection tools. This study involved 219 students (32.87% male, 67.12 % female) aged 18-20 years (M_age= 19.06, SD= 1.59) as participants. Three scales were used, namely the career exploration scale, career aspiration scale, and perceived future employability scale, and the data were analyzed using linear regression with SPSS version 22.0 for windows. The results showed that perceived future employability and career aspiration were significantly related to career exploration. Together, perceived future employability and career aspiration contributed 26.4% to career exploration. Separately, perceived future employability showed a positive relationship with career exploration, whereas career aspiration did not show a significant relationship. These findings have implications on how parents, educational institutions, and career counselors may assist students in enhancing career exploration through improving perceived of future employability.